Determinants Of Individual’s Intention To Use Islamic Home Financing Among Industrial Manufacturing Workers - Hafirda Akma, Musaddad (2019)
Nowadays, household have some difficulties in purchasing a house at the market price due to the several reasons. They need to undergo lot of procedures and conditions applied to obtain loan from the financial institutions to support their affordability to buy a house. This research aims to investigate the determinants of individual’s intention to use Islamic home financing among manufacturing workers in semiconductor industry located in Kota Bharu, Kelantan. This study measuring the factors of attitude, subjective norms, service provision, religious obligation and pricing that can influence the intentions of individuals. Samples were taken from 280 respondents who have experienced purchasing house in Kota Bharu Kelantan. The methodology used in this research is Mann Whitney U-Test, Kruskal-Wallis, Pearson Coefficient and Multiple Regression. Result of this study shows there is significant relationship between attitude, subjective norms, service provision, religious obligation and pricing with the individual’s intention to use Islamic home financing. Thus, this research provides useful information to community by increasing their level of confidence towards Islamic home financing. From this study, the researcher also suggested that bank manager need to improve various factors such as marketing, operational and customer service in order to attract more customers to purchase their products. Therefore, this study provided great contributions, implications and has recommended for financial institutions on how to improve Islamic home financing.